2014
DOI: 10.3389/fonc.2014.00364
|View full text |Cite
|
Sign up to set email alerts
|

The Host Microenvironment Influences Prostate Cancer Invasion, Systemic Spread, Bone Colonization, and Osteoblastic Metastasis

Abstract: Prostate cancer (PCa) is the second leading cause of cancer death in men worldwide. Most PCa deaths are due to osteoblastic bone metastases. What triggers PCa metastasis to the bone and what causes osteoblastic lesions remain unanswered. A major contributor to PCa metastasis is the host microenvironment. Here, we address how the primary tumor microenvironment influences PCa metastasis via integrins, extracellular proteases, and transient epithelia-mesenchymal transition (EMT) to promote PCa progression, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 234 publications
0
58
0
1
Order By: Relevance
“…This is a complex mechanism, not yet fully understood and involving many non-tumoral cell types and a cascade of events mediated by several cytokines and chemokines that drive PCa metastasis to the bone. Hormones and peptides derived from cancer cells drive osteoblasts to produce RANKL for bone resorption (72).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a complex mechanism, not yet fully understood and involving many non-tumoral cell types and a cascade of events mediated by several cytokines and chemokines that drive PCa metastasis to the bone. Hormones and peptides derived from cancer cells drive osteoblasts to produce RANKL for bone resorption (72).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Why PCa prefers bone as a site for metastasis, why metastasis is predominantly blastic, and what initiates tumor metastasis remain partially unexplained (72).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Once homed to bone marrow, tumor cells have been shown to interact with MSC or with their progeny (such as osteoblasts and adipocytes) to induce both pro-tumorigenic and inhibitory effects [81][82][83]. In light of such findings, it is clear that early crosstalk between disseminated tumor cells and the bone microenvironment is key to metastatic activation and disease progression [84], highlighting an urgent unmet need for adequate models of the disease.…”
Section: Bone Metastatic Diseasementioning
confidence: 99%
“…Studies have also shown that bidirectional EphB4-ephrin-B2 signalling has a paracrine role in osteoclast and osteoblast communication, regulating differentiation and bone formation/resorption. This is particularly interesting since PCa metastases usually occur within the bone [115]. Bone homeostasis relies on an intricate balance between bone-resorbing osteoclasts, which express ephrin-B2, and bone-forming osteoblasts, which express EphB4 [115,116].…”
mentioning
confidence: 99%
“…This is particularly interesting since PCa metastases usually occur within the bone [115]. Bone homeostasis relies on an intricate balance between bone-resorbing osteoclasts, which express ephrin-B2, and bone-forming osteoblasts, which express EphB4 [115,116]. EphB4 and ephrin-B2 have an imperative role in regulating the differentiation of osteoclasts and osteoblasts through suppression of bone resorption and enhancing bone formation [116].…”
mentioning
confidence: 99%